2020
DOI: 10.3390/microorganisms8081148
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the Treatment of Overweight and Obesity in Humans—A Review of Clinical Trials

Abstract: The World Health Organization (WHO) reports that 400 million people are obese, and over 1.6 billion adults are overweight worldwide. Annually, over 2.8 million people die from obesity-related diseases. The incidence of overweight and obesity is steadily increasing, and this phenomenon is referred to as a 21st-century pandemic. The main reason for this phenomenon is an easy access to high-energy, processed foods, and a low-activity lifestyle. These changes lead to an energy imbalance and, as a consequence, to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 127 publications
(139 reference statements)
2
55
0
Order By: Relevance
“…Accordingly, dietary interventions, including pre-and probiotics have been used to influence these parameters via modulation of gut microbiota composition in overweight and obese individuals, as well as in malnourished patients [24][25][26][27]. Several conventional probiotics have been proposed for obesity, including Lactobacillus (L. casei, L. gasseri, L. plantarum, L. rhamnosus) and Bifidobacterium (B. infantis and B. longum) species [11,[28][29][30]. However, until now, the mechanisms by which these strains may reduce excess weight remain unclear and their clinical efficacy has not yet been demonstrated convincingly [11,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, dietary interventions, including pre-and probiotics have been used to influence these parameters via modulation of gut microbiota composition in overweight and obese individuals, as well as in malnourished patients [24][25][26][27]. Several conventional probiotics have been proposed for obesity, including Lactobacillus (L. casei, L. gasseri, L. plantarum, L. rhamnosus) and Bifidobacterium (B. infantis and B. longum) species [11,[28][29][30]. However, until now, the mechanisms by which these strains may reduce excess weight remain unclear and their clinical efficacy has not yet been demonstrated convincingly [11,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms involved in the reduction of BMI after probiotic intake is the regulation of gut microbiota. Obesity favors a change of the gut microbiota composition, which can affect the energy harvest from food, the secretory functions and the composition of adipose tissue, the metabolism of carbohydrates and lipids in the liver and could also influence the activity of specific centers in the brain [ 51 ]. The regulation of gut microbiota by means of probiotics is attained by enhancing the epithelial barrier integrity, increasing adhesion to intestinal mucosa (e.g., by increasing the amount of Akkermansia muciniphila ), producing health-promoting and antimicrobial substances, excluding pathogenic microbes, and regulating the host immune system [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity favors a change of the gut microbiota composition, which can affect the energy harvest from food, the secretory functions and the composition of adipose tissue, the metabolism of carbohydrates and lipids in the liver and could also influence the activity of specific centers in the brain [ 51 ]. The regulation of gut microbiota by means of probiotics is attained by enhancing the epithelial barrier integrity, increasing adhesion to intestinal mucosa (e.g., by increasing the amount of Akkermansia muciniphila ), producing health-promoting and antimicrobial substances, excluding pathogenic microbes, and regulating the host immune system [ 51 , 52 ]. An increase in the amount of Firmicutes to Bacteroidetes leads to methylation of the obesity- and CVD-related genes and influences the activity of hormones affecting the metabolic function by increasing the ability to harvest energy [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the World Health Organization (WHO) reported that 400 million people are obese, and over 1.6 billion adults are overweight worldwide [1]. Obesity is caused by fat accumulation due to excess calorie intake or inadequate energy consumption and has been shown to increase the risk of developing various diseases, including diabetes, hypertension, and hyperlipidemia [26].…”
Section: Introductionmentioning
confidence: 99%